Epidemiological study of thermophlic Campylobacter isolated from diarrheic and non diarrheic cows in Baghdad governorate: Abdulameer Jawad Aldrajii 1 and Saleem Amin Hasso2 - Hasso, Saleem Amin (The Iraqi Journal of Veterinary Medicine, 2018)
The study achieved isolating Campylobacter spp from diarrheic and non-diarrheic cows and studying the percentage of diarrhea in 10 areas in Baghdad governorate (AL Shaeluh, Abou Ghurayb , Khadmyia , Sadar city , Suwyria, Mahmudyia, Latifyia , Alridwaniuh, Hur Rajb and Yousfyia), One thousand fecal samples were cultured on different selective culture media specific for Campylobacter spp ,and different biochemical tests were used (oxidase reaction, Oxoid biochemical identification system campy, Tripple Sugar Iron ( TSI) , hippurate hydrolysis and the use of Vietik (NH). Eighty isolates of Campylobacter spp were recorded ( 8% ).Campylobacter spp isolates included C. jejuni 30(3%) C. coli 30(3%) and C.lari 20(2%). High percentage of diarrhea was recorded in Hur rajb and Abou Ghurayb 70(82.35%) , 81 (81.81 %) respectively while lower percentage of diarrhea was in Mahmudyia and Yousfyia in percentage 43(39.09%).50(46.72%), High percentage of campylobacter isolates was recorded in AL shaeluh 15 (18.75%) , while lower percentage of isolates was recorded in Hur rajb and Yousfyia 5(6.25%), 4(5%) respectively . Age group one day to one month gave the highest isolation rate 50 %(40) while lowest isolation rate in age group(6 months to 1year) 5% ( 4) under (P ˂0.0001) level. The highest isolation rates were recorded in Summer 2016(19.16%) and Summer 2017 (24.32%) while the lowest isolation rates was recorded in Winter (0.8%). Animals infected with C. jejuni and C coli , showed obvious clinical signs including depression, loss of appetite and inability to feed newborn calves, they suffered from severe diarrhea and dehydration, and the presence of blood and thick mucus , high fever were observed in some animals, while in animals infected with C.lari the clinical signs, were mostly within normal limits .It can be concluded that two species of campylobacter( C.coli and.C. Lari) isolated from diarriheic cows,are new species added to the two species of campylobacter (C. fetus and C.Jejuni) previously isolated from cows in Iraq and increasing the total campylobacter species confirmed in Iraq to four spp.